Artificial Intelligence Deepfake Against Cybercrime Threats - Azhar, Faqih; Sulaimah, Sulaimah; Imawan, Khaerudin; Hermawan, Abdul Jalil (Indonesian Journal of Advanced Research, 2025)
This research aims to determine the practice of artificial intelligence in deepfake applications against cybercrime threats. Current technological developments have given rise to communication media using artificial intelligence technology in deepfake applications. The deepfake application can change a person’s visual and audio using a deep learning system and is widely used by the public and business actors. However, this technology often leads to cybercrime such as fraud and identity theft. This study uses a descriptive qualitative method with data collection through literature review and analysis descriptively. The findings answer problems related to fraud and identity theft, focusing on the East Java Governor case, and emphasize the need for preventive measures by the public and government to avoid misuse of deepfake applications.